Differential gene expression profile and altered cytokine secretion of thyroid cancer cells in space. Issue 2 (6th November 2013) - Ma, Xiao; Pietsch, Jessica; Wehland, Markus; Schulz, Herbert; Saar, Katrin; Hübner, Norbert; Bauer, Johann; Braun, Markus; Schwarzwälder, Achim; Segerer, Jürgen; Birlem, Maria; Horn, Astrid; et al.
Abstract : This study focuses on the effects of short‐term [22 s, parabolic flight campaign (PFC)] and long‐term (10 d, Shenzhou 8 space mission) real microgravity on changes in cytokine secretion and gene expression patterns in poorly differentiated thyroid cancer cells. FTC‐133 cells were cultured in space and on a random positioning machine (RPM) for 10 d, to evaluate differences between real and simulated microgravity. Multianalyte profiling was used to evaluate 128 secreted cytokines. Microarray analysis revealed 63 significantly regulated transcripts after 22 s of microgravity during a PFC and 2881 after 10 d on the RPM or in space. Genes in several biological processes, including apoptosis ( n =182), cytoskeleton ( n =80), adhesion/extracellular matrix ( n =98), proliferation ( n =184), stress response ( n =268), migration ( n =63), angiogenesis ( n =39), and signal transduction ( n =429), were differentially expressed. Genes and proteins involved in the regulation of cancer cell proliferation and metastasis, such as IL6, IL8, IL15, OPN, VEGFA, VEGFD, FGF17, MMP2, MMP3, TIMP1, PRKAA, and PRKACA, were similarly regulated under RPM and spaceflight conditions. The resulting effect was mostly antiproliferative. Gene expression during the PFC was often regulated in the opposite direction. In summary, microgravity is an invaluable tool for exploring new targets in anticancer therapy and can be simulated in some aspects in ground‐based facilities.—Ma, X., Pietsch, J., Wehland, M., Schulz, H., Saar, K., Hübner, N., Bauer, J., Braun, M., Schwarzwälder, A., Segerer, J., Birlem, M., Horn, A., Hemmersbach, R., Waβer, K., Grosse, J., Infanger, M., Grimm, D. Differential gene expression profile and altered cytokine secretion of thyroid cancer cells in space. FASEB J. 28, 813–835 (2014). www.fasebj.org